2008
DOI: 10.1152/physiolgenomics.00222.2007
|View full text |Cite
|
Sign up to set email alerts
|

Functional polymorphisms in inbred rat strains and their allele frequencies in commercially available outbred stocks

Abstract: Polymorphisms that have been proven to influence gene functions are called functional polymorphisms. It is significant to know the distribution of functional polymorphisms in the rat, widely used in animal models for human diseases. In this study, we assessed 16 functional polymorphisms consisting of 3 coat color and 13 disease-associated genes in 136 rat strains, as a part of the genetic profiling program of the National Bio Resource Project for the Rat (NBRP-Rat). Polymorphisms of Cdkn1a, Fcgr3, Grp10, Lss, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 26 publications
(25 reference statements)
1
9
0
Order By: Relevance
“…Several functional polymorphisms in the rat genome have already been reported. A total of 16 functional polymorphisms linked to three coat color and 13 disease-associated genes in inbred rat strains have been characterized altogether with their allele frequencies in commercially available outbred stocks (22). Other examples of naturally occurring inactivating SNPs or gene insertion/deletion associated with marked phenotypic change have also been discovered in rat.…”
Section: Discussionmentioning
confidence: 99%
“…Several functional polymorphisms in the rat genome have already been reported. A total of 16 functional polymorphisms linked to three coat color and 13 disease-associated genes in inbred rat strains have been characterized altogether with their allele frequencies in commercially available outbred stocks (22). Other examples of naturally occurring inactivating SNPs or gene insertion/deletion associated with marked phenotypic change have also been discovered in rat.…”
Section: Discussionmentioning
confidence: 99%
“…We first investigated the distribution of Fcgr3-rs deletion throughout the rat phylogeny and found that the deletion was widespread. It was previously reported that five outbred Wistar and one Long-Evans stocks have Fcgr3-rs (23), suggesting that the deletion has originated from the ancestor outbred Wistar colony in the Wistar institute in the United States. We now confirm and extend these findings because all of the laboratory rat strains that we genotyped for Fcgr3 copy number variation are derived from outbred Wistar and Long-Evans stocks.…”
Section: Discussionmentioning
confidence: 99%
“…NBRP-Rat has recently surveyed 140 rat strains for gene mutations reported in particular rat strains that are responsible for functional polymorphisms (Fig. 3) [9]. Forty-nine rat strains show the insertion type of Cdkn1a/p21 [29], suggesting their resistance to prostate cancer; 79 rat strains have the duplication type of Fcgr3 [1], suggesting their resistance to experimentally induced nephritis; and 63 and 29 rat strains have point mutations of Lss and Fdft1 [17], respectively, suggesting their susceptibility to cataracts.…”
Section: Functional Polymorphismsmentioning
confidence: 99%
“…Such information is very helpful for selecting suitable rat strains for particular experiments. Since functional polymorphisms were also found in outbred or closed colonies at different rates among rat colonies [9], we recommend that testing or experiments with rats should be planned after giving careful consideration to this issue.…”
Section: Functional Polymorphismsmentioning
confidence: 99%